Development of a software application for teaching computer networking - Liu, Bi Hao (Nanyang Technological University, 2021)
Positive effects of learning through interactive activities had been widely recorded across the globe. Research has shown that interactive learning has beneficial effects on areas of learning such as memory, motivation, and confidence. Students are also shown to be more engaged in their studies when properly engaged with their mentor and peers, hence reducing truancy rates and destructive behaviors. Shifting the attention back to today’s society, the evolution of the Internet and its relevancy far exceeds expectations of expects. In a short span of 30 years, the internet has seen exponential growth and along with it the protocols that connect with it. 5G technology is slowly making its way into the market, improving the speed and utility of the internet. Internet of things is becoming a reality and with it comes along several problems such as data speed and IP address licenses. The current and the next generations need to understand computer networking to fully utilize the technology of tomorrow, and that is the goal of this project. This project will focus on the development process of a teaching application intended to teach the generic audience about internet networking through the TCP/IP protocol. This report will detail the entire development process, which includes market research, conceptualizing, designing, and developing the application.